2007
DOI: 10.1111/j.1574-6968.2007.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of lactobacilli isolated from salami

Abstract: Sixty-five strains of lactobacilli isolated from salami were tested for their antifungal activity in early and late phases of growth. Ten strains showed inhibitory activity in the early phase of growth towards moulds such as Aspergillus and Penicillium. The active compounds identified were phenyl-lactate and hydroxy-phenyl-lactate. All strains tested had activity in the late phase, after autolysis. The compounds released were peptidic and showed antifungal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 25 publications
3
26
0
1
Order By: Relevance
“…This was also observed in previous studies (Coloretti et al, 2007). But using 30 days of incubation would be too long to favor cell autolysis.…”
Section: Anti--mold Activity Of Supernatant and The Physicochemical Csupporting
confidence: 66%
See 4 more Smart Citations
“…This was also observed in previous studies (Coloretti et al, 2007). But using 30 days of incubation would be too long to favor cell autolysis.…”
Section: Anti--mold Activity Of Supernatant and The Physicochemical Csupporting
confidence: 66%
“…Corsetti et al (1996) isolated a bacteriocin--like inhibitory substance from Lactobacillus sanfrancisco C57, and found that all the antimicrobial compounds produced from strain contained a protein moiety and were sensitive to different proteinases. Coloretti et al (2007) studied the antifungal activity of lactobacilli isolated from salami and reported that at the end of cell growth, more peptidic compounds that sensitive to the action of proteinase K were released. Coda et al (2008) identified a mixture of eight peptides from the water--soluble extract of sourdough L. brevis AM7, and 5 of these exhibited inhibitory activity.…”
Section: Proteinaceous Compoundsmentioning
confidence: 99%
See 3 more Smart Citations